L`artère d`athlète : remodelage de l`artère brachiale chez des sportifs d`élite pratiquant différents sports - Di Gioia, G.; Vespasiano, F.; Ferrera, A.; Segreti, A.; Lemme, E.; Squeo, M. R. (Science & Sports, 2025)
Aims Exercise training impacts arterial remodeling but a research gap remains on the effects of various training modalities. Therefore, we have evaluated the influence of different disciplines (power, skills, endurance, mixed) on brachial adaptation in 122 athletes. Methods and results The were divided into: Group1 (active arm involvement) and Group2 (control group). Endurance had the largest brachial arterial diameter (BAD). Additionally, Group1 showed a significantly larger BAD, mainly due to endurance adaptations. No differences were found in flow-mediated-dilation (FMD) between disciplines and between Group1 vs. Group2. Conclusion Vascular adaptation is peculiar of endurance athletes, characterized by BAD enlargement (proportional to the vascular district used) without affecting function.